A selenophene substituted diketopyrrolopyrrole nanotheranostic agent for highly efficient photoacoustic/infrared-thermal imaging-guided phototherapy. Issue 1 (3rd October 2017) - Cai, Yu; Liang, Pingping; Si, Weili; Zhao, Baomin; Shao, Jinjun; Huang, Wei; Zhang, Yewei; Zhang, Qi; Dong, Xiaochen
Abstract : A selenophene substituted diketopyrrolopyrrole based nanotheranostic agent has been synthesized for highly efficient photoacoustic/infrared-thermal imaging-guided tumor phototherapy. Abstract : Phototherapy, a light-induced cancer therapy, has presented great promise for multimodal cancer treatment. Herein, a selenophene substituted diketopyrrolopyrrole based nanotheranostic photosensitizer (SeDPP-TPA) has been designed and synthesized. The introduction of selenophene enables SeDPP-TPA to produce a high yield of singlet oxygen ( 1 O2 ) ( Φ Δ = 40.2%), and show a bathochromic shift in absorbance ( λ max at 648 nm), enhanced charge transfer and biocompatibility. After nanoprecipitation, SeDPP-TPA nanoparticles (NPs) are prepared with excellent water dispersibility and passive tumor-targeting properties based on the enhanced permeability and retention effect. Besides, SeDPP-TPA NPs present a high photothermal conversion efficiency ( η = 37.9%). An in vitro cytotoxicity test shows that the half-maximal inhibitory concentration (IC50 ) of SeDPP-TPA NPs on tumor cells is ∼12 μg mL −1, indicating their excellent phototherapy efficiency. What is more, because of the thermal expansion and tumor-targeting properties, SeDPP-TPA NPs can also act as a contrast agent for photoacoustic imaging to visualize the therapy in vivo . Coupled with the infrared thermal imaging properties of the photothermal agent, SeDPP-TPA NPs are proved to be a multifunctional theranostic agent for dual-modal imaging-guided phototherapy.